Analisis Pengaruh Efektivitas Penagihan, Penyertaan Modal Daerah dan Air Tak Berekening terhadap Kontribusi Pendapatan Asli Daerah dengan Return on Equity (ROE) sebagai Variabel Intervening: - Ova Tri Nugroho; Sri Hermuningsih; Gendro Wiyono (Reslaj : Religion Education Social Laa Roiba Journal, 2023)
The purpose of this study is to analyze the effect of billing effectiveness, participation of regional capital and non revenue water on the contribution of local native income with return on equity (ROE) as an intervening variable: a case study on the General Company of Magelang City Drinking Water Area. The data is secondary data, namely the monthly financial statements published by the General Company of magelang City Drinking Water Area for the period 2016-2021. The data analysis method used is descriptive analysis and inferential analysis with the help of analytical tools used is Patial Least Square (PLS), which is SEM based on variance, with SmartPLS software. Analysis using PLS there are several things that are done, namely the fit model test, hypothesis test and mediation test. The waiting results showed that the effectiveness of billing and non revenue water had an insignificant negative effect on PAD contributions, capital participation had a significant negative effect on PAD contributions, the effectiveness of billing and non revenue water had an insignificant negative effect on returns on equity, capital participation had an insignificant positive effect on returns on equity, returns on equity had a positive effect on returns on equity. significant to the contribution of PAD. Based on mediation analysis states that intervening variables (returns on equity) insignificantly have a decreased effect on the influence between billing effectiveness on PAD contributions. And for intervening variables (returns on equity) significantly give an increased effect on the influence between capital participation on PAD contributions. While intervening variables (returns on equity) do not significantly have a decreased effect on the influence between non revenue water on the contribution of PAD. Keywords: billing effectiveness; capital participation; non revenue water, return on equity and PAD contribution